2007
DOI: 10.1080/10715760701348611
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and properties of novel powerful antioxidants, glutathione analogues

Abstract: Glutathione (GSH) is the major low-molecular weight antioxidant in mammalian cells. Thus, its analogues carrying similar and/or additional positive properties might have clinical perspectives. Here, we report the design and synthesis of a library of tetrapeptidic GSH analogues called UPF peptides. Compared to cellular GSH our designed peptidic analogues showed remarkably higher hydroxyl radical scavenging ability (EC(50) of GSH: 1,231.0 +/- 311.8 microM; EC(50) of UPF peptides: from 0.03 to 35 microM) and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Both compounds are linked to each other by using a covalent bond that is cleavable which regenerates the original drug with adequate bioavailability. Investigations in this type of compounds have already been reported (Ehrlich et al, 2007). In addition, as we have described, oxidative stress produces methionine sulfoxide, which is epigenetically toxic.…”
mentioning
confidence: 88%
“…Both compounds are linked to each other by using a covalent bond that is cleavable which regenerates the original drug with adequate bioavailability. Investigations in this type of compounds have already been reported (Ehrlich et al, 2007). In addition, as we have described, oxidative stress produces methionine sulfoxide, which is epigenetically toxic.…”
mentioning
confidence: 88%
“…The enzyme free hydroxyl radical scavenging assay showed that substitution of g-glutamyl moiety (UPF1) with a-glutamyl moiety (UPF17) improved hydroxyl radical scavenging activity  500-fold [25].…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed synthesis protocol of UPF peptides has been published before [25,28]. The purity of the peptides was !99%, as demonstrated by HPLC on an analytical Nucleosil 120-3 C18 reversed-phase column (0.4 cm)10 cm).…”
Section: Peptide Synthesismentioning
confidence: 99%
See 2 more Smart Citations